ANALISIS STRATEGI PEMASARAN LAYANAN BABY CARE DI RSU BHAKTI RAHAYU DENPASAR TAHUN 2020 - Semarajana, I Nyoman Gede; Maharjana, Ida Bagus Nyoman (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
Baby massage has long been known to be beneficial in helping baby's growth and development and is a hereditary tradition. The benefits of baby massage have been shown in various studies, but the lack of mother's knowledge about how to properly massage a baby also encourages mothers to seek baby massage services to both shamans and baby spas. These factors enable Bhakti Rahayu Hospital to develop Baby Care services in 2020 as a form of continuity of services provided to post-partum mothers. The purpose of this study was to analyze the marketing strategy of Baby Care services at Bhakti Rahayu Denpasar Hospital in 2020. The research design used was descriptive with a cross-sectional approach. Analysis was carried out by segmenting, targeting, and positioning of the Baby Care service, followed by determining the 4P (Product, Price, Place, and Promotion) marketing mix. Baby Care service has eight products at affordable and competitive prices, and activities carried out at home will make it easier for mothers to get services. Promotion of Baby Care services needs to be expanded and further evaluation needs to be done so that it can be known about the utilization of Baby Care services at Bhakti Rahayu Hospital Denpasar